Diiridium(iii) complexes: luminescent probes and sensors for G-quadruplex DNA and endoplasmic reticulum imaging. (12th December 2016) - Anjong, Tikum Florence; Kim, Gyoungmi; Jang, Ha Yoon; Yoon, Juyoung; Kim, Jinheung
Abstract : Two new dinuclear iridium (Ir) complexes bridged by a conjugated aromatic tppz ligand, (bhq)2 Ir(tppz)Ir(bhq)2 (1 ) and (ppy)2 Ir(tppz)Ir(ppy)2 (2 ) (bhq = benzo( h )quinolone, ppy = phenyl-pyridine, tppz = tetrapyrido[3, 2- a :2′, 3′- c :3′′, 2′′- h :2′′′, 3′′′- j ]phenazine), were prepared. Abstract : Two new dinuclear iridium (Ir) complexes bridged by a conjugated aromatic tppz ligand, (bhq)2 Ir(tppz)Ir(bhq)2 (1 ) and (ppy)2 Ir(tppz)Ir(ppy)2 (2 ) (bhq = benzo( h )quinolone, ppy = phenyl-pyridine, tppz = tetrapyrido[3, 2- a :2′, 3′- c :3′′, 2′′- h :2′′′, 3′′′- j ]phenazine), were prepared. The DNA binding properties of complexes1 and2 were studied using single-stranded DNA, double-stranded DNA, and G-quadruplex DNA. G-Quadruplex binding was characterized by higher emission enhancements than those observed with other control DNA strands. Photophysical properties of complexes1 and2 indicated that1 displayed selective G-quadruplex binding affinity, but2 did not. The emission properties of complexes1 and2 were also studied using liposomes in order to understand their possible interactions with lipid-rich organelles in live cells. The phosphorescence intensity of1 and2 was enhanced upon interaction with liposomes, but2 showed greater enhancement. We also confirmed that1 and2 could be used as probes in live cells. Complexes1 and2 were intensely stained in HeLa cervical cancer cells. Excitation with a λ = 488 nm laser showed red emission localized in the cytosol of cells. Cellular studies showed that1 and2 were located inside HeLa cells, but neither complex passed through the nuclear membrane. However, complexes1 and2 possessed superior photostability, indicating their role as good luminescent agents for imaging and tracking the endoplasmic reticulum (ER) in live cells. Overall, complex1 exhibited better selectivity for G-quadruplexes, liposomes, and ER staining.